Export Competitiveness : Why Domestic Market Competition Matters - Goodwin, Tanja; Pierola, Martha Denisse (World Bank, Washington, DC, 2016)
This review of the empirical literature shows that industries with more intense domestic competition will export more. Competition law enforcement can be traced to export performance and is complementary to trade reforms. Pro-competition market regulation that reduces restrictions and promotes competition, where it is viable, is an important determinant for trade. The elimination of barriers to entry and rivalry, and a level playing field in upstream sectors contributes to export competitiveness in downstream manufacturing sectors. In some sectors, effective competition policy can directly lower trade costs.